THE EFFECTIVENESS OF THE TOURISM AWARENESS EDUCATION MODEL FOR COMMUNITY-BASED TOURISM OBJECT MANAGERS IN AGAM DISTRICT, WEST SUMATRA, INDONESIA - Rahmi Novalita; Ahyuni Ahyuni; Mona Adria Wirda; Afrital Rezki (Universitas Negeri Medan, 2021)
This research aims to describe the design of the community-based tourism awareness education model and the effectiveness of the tourism awareness education model. This research is included in the Research and Development (R&D) type of research utilizing the ADDIE model. The population was a community-based tourist attraction manager, amounting to 20 people with the incidental sampling technique, divided into 2 groups. The results showed that: 1) the design of a community-based tourism awareness education model consisted of; candidate participants and selection of potential participants with the preparation stage including; a) objectives, materials, strategies, procedures, media, teaching materials, evaluation, b) socialization of program introduction, c) program implementation, and d) mentoring; 2) the effectiveness of the community-based tourism awareness education model was seen from the test results of participants which showed that there were differences in the results before and after education, where after education a higher average value was obtained, with a smaller standard deviation. Although divided into 2 groups, the educational results showed no significant difference between the post-test scores in group 1 and group 2. This proves that education has been effective in providing awareness for community-based object managers.Keywords: Effectiveness, Tourism Awareness Education Model, Community-based Tourism Object Manager, ADDIE Model